Synopsis of the genus Atriplex (Amaranthaceae, Chenopodioideae) for South America - Brignone, Nicolás Fernando (2016)
This is the first integrative synopsis of the genus Atriplex L. for South America, based on the study of compared external morphology of extensive collections from South American herbaria, type material, digital images, original publications and field observations. The South American Atriplex flora includes 55 species, 45 of which are native species, mainly distributed in Argentina and Chile (a few of them growing in Bolivia, Ecuador, Paraguay, Peru, Uruguay and Venezuela), and 10 are adventive species. We accept two subspecies for Atriplex cordubensis Gand. & Stuck., namely, subsp. cordubensis and subsp. grandibracteata Múlgura, two varieties for A. imbricata D.Dietr., var. imbricata and var. foliolosa Rosas, proposed one new synonym for A. deserticola Phil., one nomenclatural change for A. mucronata Phil., and designate 19 lectotypes and one second-step lectotype for A. nummularia Lindl. This synopsis also includes a key to the 55 South American species, three new figures for A. asplundii Standl., A. oestophora S.F.Blake and A. rusbyi Britton, references for previous figures of the remaining species, illustrations of different positions of the radicle in the seeds, maps of distribution, taxonomic and morphological notes, and a complete list of material studied.